Língua, sujeito e enunciação em "Memorial de Maria Moura": deslizamentos metonímicos e metafóricos - Gomes, Maria José Pereira (2009)
This dissertation is an object of study between three areas of knowledge. Thus, the goal has generally, to investigate the relationship of language, and the subject of enunciation in Memorial of Maria Moura. And as specific objectives: a) understand the concept of language in this work, linking it to the notion of alíngua b) examine the slide of the names of the axes through metaphorical metonymy and c) studying the subject of the unconscious, linking it to movement of the tongue / alingua for the composition of the novel. Thus was developed a theoretical and empirical qualitative research, the methodological procedures adopted consisted in bringing categories of analysis derived from theories of Saussure, Benveniste, Jakobson, Lacan, Freud, and the work of Milner (1987), Authier-Revuz ( 1998-2004), among others. Considering that, on language, might be thought that linguists seek to convey the current functioning of language itself, however, regarding the functioning of poetic language, this bias is seen by the deviation of the slide and therefore conceived as a manifestation of linguistic practice. It would be his own literary creation, as expressions of an experience of language, an important contribution to a theory of language. With regard to the relationship between language and psychoanalysis, according to Flores (2002), there is a link without many problems, since the interest of the language is made since the first texts of Freud. Thus, a relationship that is established by the study of the subject and the sense to do so, remember Milner (1987), in the love of language, bringing some language issues, impossible to be described without having to do that, there is the intervention of the subject - the Lacanian subject. Dealing with issues of language, and the subject of enunciation, in a separate crossover of knowledge: the language, literature, and Lacanian psychoanalysis, finding them, anchor points in common, and even differences in the treatment of the phenomenon addressed, if the constitution the subject of the unconscious as a subject of enunciation. However, the interaction between linguistic and other fields of knowledge has been a controversial topic, it should be noted that, starting a research study involving the analysis of literary language long represented a task of risk, because as Maingueneau (1996, p. 1), the relationship between language and Analysis of Literature are not a clear, above all, separated by a gap. To some, the relationship between linguistics and literature is usually seen as unilateral, that is what is sought is the contribution of the science of language to understand the literary text